Pelatihan Komputer sebagai Bentuk Pengembangan Nilai-Nilai Karakter dalam Bidang Pendidikan - Supardi Supardi; Nurul Hikmah Kartini; Agustina Fatmawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The result of the analysis of the studyshows the lack of educational condition related to Information Technology (IT) especially for orphanage children. Community service activities aim to provide computer training as a form of character development in the field of education. The subjects of community service activities are the children at the Mujahidin Orphanage in Anjir Serapat Village, Kapuas Timur Sub-District, Kapuas District, with 11 members. Training activities are supported by lecture methods, frequently asked questions and direct practice of using computer applications with the help of training modules provided to the participants as a tool in practice. The results showed that computer training can give knowledge and understanding for orphaned children in computer skills in the mastery of Microsoft Word, Microsoft Excel, and Microsoft Powerpoint and can foster the values of educational characters in themselves such as curiosity, creative, hard work, and communicative.